Development and Evaluation of an E-learning System using the CodeIgniter framework to Support Informatics Learning at SMA Negeri 1 Tanjung Raja - Rosdiyanna Safitri; Rangga Firdaus; Nurain Suryadinata (LPPM Universitas Bhinneka Nusantara, 2026)
This study aims to develop and evaluate a web-based e-learning system to support Informatics learning at SMA Negeri 1 Tanjung Raja. The research employed a Research and Development (R&D) approach using the Waterfall model, consisting of requirements analysis, system design, implementation, testing, and maintenance. The system was developed using the CodeIgniter 4 framework with the Model–View–Controller (MVC) concept. Functional testing was conducted using the Black Box Testing method, executed on 13 different test scenarios by three expert validators with information technology education lecturers with backgrounds in software engineering. All 13 test items were evaluated independently by each validator, resulting in a 100% pass rate (13 out of 13 items were functional in the third validator). Usability testing using the System Usability Scale (SUS) instrument with 30 respondents comprising 29 Grade X students and 1 Informatics teacher, resulted in an average SUS score of 89, which is classified as Very Good. These findings indicate that the system has robust functionality and is considered very easy to use in this particular school context. Limitations include the single-school setting and relatively small sample size, and further validation across different educational contexts is recommended.